2022
DOI: 10.1371/journal.pntd.0010774
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine protease of Clonorchis sinensis alleviates DSS-induced colitis in mice

Abstract: Background Currently, inflammatory bowel disease (IBD) has become a global chronic idiopathic disease with ever-rising morbidity and prevalence. Accumulating evidence supports the IBD-hygiene hypothesis that helminths and their derivatives have potential therapeutic value for IBD. Clonorchis sinensis (C. sinensis) mainly elicit Th2/Treg-dominated immune responses to maintain long-term parasitism in the host. This study aimed to evaluate the therapeutic effects of cysteine protease (CsCP) and adult crude antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Dexamethasone is commonly used for the treatment of colitis in mice and humans. In this study, it was employed as a positive control reagent for mice and administered via intraperitoneal injection [ 19 ]. We found that compared with the DSS group, the administration of miR-31-5p antagomir significantly reduced the DAI score [ 20 ] ( P < 0.05) ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Dexamethasone is commonly used for the treatment of colitis in mice and humans. In this study, it was employed as a positive control reagent for mice and administered via intraperitoneal injection [ 19 ]. We found that compared with the DSS group, the administration of miR-31-5p antagomir significantly reduced the DAI score [ 20 ] ( P < 0.05) ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…This can be explained by the reduction in inflammation of AA-induced colitis offered by intraperitoneal delivery of T. spiralis -produced antigens. In mice treated with Clonorchis sinensis cysteine protease, Xie et al (2022) also observed a significantly higher survival rate for dextran sulfate sodium-induced colitis.…”
Section: Discussionmentioning
confidence: 96%
“…Mounting evidence indicates that C . sinensis infection drives Th2 immune responses and facilitates the production of the cytokines IL-13, TGF-β, IL-10 and IL-4 [ 53 , 54 ], which have been implicated in promoting cancer stemness [ 55 , 56 ]. Carlo De Salvo et al uncovered the importance of eosinophils in the early cascade leading to intestinalized metaplasia in gastritis-prone mice, suggesting a potential mechanism that contributes to the inflammation-metaplasia-dysplasia-carcinoma sequence [ 57 ].…”
Section: Discussionmentioning
confidence: 99%